Numerical Simulation Study on the Impedance of the Communication Port of Liquid Launch Vehicle Gas-Filled Accumulators - Tong Shi; Guozhu Liang; Yunqin He (Applied Sciences)
To prevent pogo oscillation in liquid launch vehicles, it is essential to install a gas-filled accumulator near the pump with minimum flow inertance and a target-design level of flow resistance, which are the real and imaginary parts of communication port impedance. However, the present approach of estimating the flow impedance of the accumulator communication port based on an orifice flow model introduces a non-negligible error, possibly leading to accumulator failure. In this study, a transient computational fluid dynamics simulation is conducted on a communication port model, where the liquid oxygen is considered incompressible and k-ε turbulence model is used. The results indicate that the formation of a vortex downstream of the communication port leads to the attenuation of its linear resistance. A method for calculating the impedance of the communication port is proposed, where the impact of supply pipeline velocity, oscillatory flow amplitude, and frequency is considered. The results indicate that the quasi-steady assumption is suitable for oscillatory flow frequencies below 14.5 Hz, with a deviation of less than 30%. Above this frequency, a linear frequency correction can be used to reduce the deviation to less than 26.5% within the pogo frequency range. The impedance calculation formulae given in this research can be used in the engineering design of the gas-filled accumulators.